Sometimes Resigned, Sometimes Conflicted, and Mostly Risk Averse: Primary Care Doctors in India as Street Level Bureaucrats - Sudha Ramani; Lucy Gilson; Muthusamy Sivakami; Nilesh Gawde (Kerman University of Medical Sciences, 2021)
BackgroundIn this study, we use the case of medical doctors in the public health system in rural India to illustrate the nuances of how and why gaps in policy implementation occur at the frontline. Drawing on Lipsky's Street Level Bureaucracy (SLB) theory, we consider doctors not as mechanical implementors of policies, but as having agency to implement modified policies that are better suited to their contexts. MethodsWe collected data from primary care doctors who worked in the public health system in rural Maharashtra, India between April and September 2018 (including 21 facility visits, 29 in depth interviews and several informal discussions). We first sorted the data inductively into themes. Then we used the SLB theoretical framework to categorise and visualise relationships between the extracted themes and deepen the analysis. ResultsDoctors reported facing several constraints in the implementation of primary care- including the lack of resources, the top-down imposition of programs that were not meaningful to them, limited support from the organization to improve processes as well as professional disinterest in their assigned roles. In response to these constraints, many doctors 'routinized' care, and became resigned and risk-averse. Most doctors felt a deep loss of professional identity, and accepted this loss as an inevitable part of a public sector job. Such attitudes and behaviours were not conducive to the delivery of good primary care. ConclusionThis study adds to empirical literature on doctors as Street Level Bureaucrats in lower and middle income countries. Doctors from these settings have often been blamed for not living up to their professional standards and implementing policies with rigour. This study highlights that doctors' behaviours in these settings are ways through which they 'cope' with their loss of professional identity and organizational constraints; and highlights the need for appropriate interventions to counter their weak motivation.